Association Between Gluteus Medius Strength and Gait Instability among University Students with BMI - Nayab John, Alina Ali, Khushboo Gulzar, Hurayra Arbab, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Gluteus Medius muscle plays an important role in stabilizing the pelvis during gait. Individuals with obesity may experience weakness in gluteus Medius and gait instability. However, it is still unclear whether the musculature of a person with obesity can compensate for these changes. Objective: To evaluate the comparison of gluteus medius strength and gait instability from university students with different BMI Methodology: This cross-sectional study was conducted. The study was completed June 2022 to October 2022 according to the rules and regulations set by the ethical committee of University Of Lahore, Gujrat campus by selecting 385 patients who cleared the inclusion and exclusion criteria. Both male and female university students were included. In this study the strength of gluteus medius was checked by using with Manual Muscle Testing Grading System (MMT). The Grading Scale Range from 0 to 5, gait instability was checked from the Gait analysis Questionnaire. Results: The results of current study shows that age of participants were 23.06±2.49, gender of participants were 1.30±0.46. BMI class * Manual Muscle Testing (Left) Cross tabulation shows that the normal (BMI Score >18.5 to 25) was 0 fair, 8 good and normal were 218, while Over Weight (BMI Score >25 to 30) were 2 fair, 11 good and 111 normal whereas Obese (BMI Score>30) got 3 fair, 15 Good and 17 Normal manual muscle testing scoring while (Right) side shows that normal (BMI Score >18.5 to 25) have 0 fair, 16 good and normal were 210, while Over Weight (BMI Score >25 to 30) have 3 fair, 21 good and 100 normal whereas Obese (BMI Score>30) got 6 fair, 9 Good and 20 Normal manual muscle testing scoring. Gait when walking through a narrow space have 373(10.2%), problems walking when getting on the lift 372(10.2%), problems walking when entering a revolving door was 374(10.2%), problem walking in crowded places 366(10.0%). Practical Implication: Scientific evidence, muscle strength is inversely and independently associated with all-cause mortality. Some authors even recommend the use of an algorithm to remove the dependence on body size and to more appropriately compare the strength of the hip muscles across individuals since it cannot be concluded that the force is directly proportional to body weight. Conclusion: There was significant correlation between BMI class and quadriceps strength. Participants with higher BMI shows less quadriceps strength than people with lesser BMI. Increased body mass, in absence of other obesity-related comorbidities, may have minimum impact on gait instability and in turn fall risk. Keywords: Gluteus, Medius, Gait Instability, BMI, muscle testing